2007
DOI: 10.1152/ajpregu.00516.2006
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor in the hypothalamic paraventricular nucleus increases energy expenditure by elevating metabolic rate

Abstract: Brain-derived neurotrophic factor (BDNF) decreases food intake and body weight, but few central sites of action have been identified. The hypothalamic paraventricular nucleus (PVN) is important in energy metabolism regulation, and expresses both BDNF and its receptor. We tested three hypotheses: 1) PVN BDNF reduces feeding and increases energy expenditure (EE), 2) PVN BDNF-enhanced thermogenesis results from increased spontaneous physical activity (SPA) and resting metabolic rate (RMR), and 3) PVN BDNF thermog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 63 publications
2
87
1
5
Order By: Relevance
“…we extend this analysis to other CNS regions, where it is known that insulin and BDNF signaling are involved in energy homeostasis (feeding behaviors, locomotor activity and metabolism), [48][49][50][51][52][53][54][55] it could be plausible that Kv-null animals have increased BDNF sensitivity in areas which normally expresses Kv1.3 13 and would be predicted to demonstrate elevated TrkB in Kv-null mice. More experiments are required to resolve a discrete mechanism that might link loss of Kv1.3 and BDNF activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…we extend this analysis to other CNS regions, where it is known that insulin and BDNF signaling are involved in energy homeostasis (feeding behaviors, locomotor activity and metabolism), [48][49][50][51][52][53][54][55] it could be plausible that Kv-null animals have increased BDNF sensitivity in areas which normally expresses Kv1.3 13 and would be predicted to demonstrate elevated TrkB in Kv-null mice. More experiments are required to resolve a discrete mechanism that might link loss of Kv1.3 and BDNF activity.…”
Section: Discussionmentioning
confidence: 98%
“…53,54,58 The PVN has also been shown to be important for mediating BDNF effects on metabolism but not locomotor activity. 52 BDNF's effects on locomotor activity are localized to the forebrain regions as revealed by forebrain-specific knockouts of bdnf 59 and its receptor, trkB.…”
Section: Discussionmentioning
confidence: 99%
“…Low BDNF expression was observed in the hypothalamus of BDNF ϩ/Ϫ heterozygous animals, including the PVN and VMH (36). Bariohay et al (3) reported significant decreases in feeding and body weight gain during chronic infusion of BDNF in the dorsal ventral complex, and our previous work (85,86) indicates that the PVN is an important site of BDNF action.BDNF in the VMH may also play an important role in the regulation of energy metabolism. Both mRNA and protein for BDNF and its receptor TrkB have been identified in the VMH (8,36,87,90).…”
mentioning
confidence: 80%
“…Low BDNF expression was observed in the hypothalamus of BDNF ϩ/Ϫ heterozygous animals, including the PVN and VMH (36). Bariohay et al (3) reported significant decreases in feeding and body weight gain during chronic infusion of BDNF in the dorsal ventral complex, and our previous work (85,86) indicates that the PVN is an important site of BDNF action.…”
mentioning
confidence: 80%
See 1 more Smart Citation